2023
DOI: 10.1021/acsanm.3c00370
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Dot-Doped Electrospun Polymer Fibers for Explosive Vapor Sensors

Dalton Ennis,
Dylan Golden,
Mackenzie C. Curtin
et al.

Abstract: This research seeks to support reconnaissance efforts against homemade explosives (HMEs) and improvised explosive devices (IEDs), which are leading causes of combat casualties in recent conflicts. The successful deployment of a passive sensor to be developed for first responders and military must take expense, training requirements, and physical burden all into consideration. By harnessing the size-dependent luminescence of quantum dots (QDs) being electrospun into polymer fibers, the authors of this work hope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…In 2021, Tawfik et al demonstrated the possibility to detect TATP in solution with polythiophene-capped CdTe CQDs, achieving a competitively low detection limit of 0.055 mg L –1 in water; the proposed device relied on an OFF-ON mechanism where the CQD PL was first quenched upon exposure to Hg 2+ ions via electron transfer, and then the PL recovery was induced by the addition of TATP to the solution. Ennis et al published a proof-of-concept study on the realization of a field-applicable sensor by electrospinning CdSe CQDs into polymer fibers and measuring the PL quenching upon exposure toward different kinds of explosive vapors including TATP and RDX, even if with very low efficiency with respect to nitroaromatic compounds . Although promising, these results need to be confirmed in validation studies.…”
Section: Luminescent Sensorsmentioning
confidence: 99%
“…In 2021, Tawfik et al demonstrated the possibility to detect TATP in solution with polythiophene-capped CdTe CQDs, achieving a competitively low detection limit of 0.055 mg L –1 in water; the proposed device relied on an OFF-ON mechanism where the CQD PL was first quenched upon exposure to Hg 2+ ions via electron transfer, and then the PL recovery was induced by the addition of TATP to the solution. Ennis et al published a proof-of-concept study on the realization of a field-applicable sensor by electrospinning CdSe CQDs into polymer fibers and measuring the PL quenching upon exposure toward different kinds of explosive vapors including TATP and RDX, even if with very low efficiency with respect to nitroaromatic compounds . Although promising, these results need to be confirmed in validation studies.…”
Section: Luminescent Sensorsmentioning
confidence: 99%